Pharma Collaboration for Transparent Medical Information (phactMI) Benchmark Study: Trends, Drivers, Success Factors, and Value of Globalization in Medical Information. (May 2019) - Giffin, Suzana A.; Shah, Richa; Soloff, Allison; Vaysman, Anna Markel; Oreper, Jane; Gažo, Andrew; Gandhi, Pooja; Shah, Ina; Malieckal, Thomas; Boulos, Daniel; Flowers, Teresa; Stevens, Carolle A.; et al.
Background: Over the past decade, biopharmaceutical companies have been progressively establishing global frameworks across their capabilities. It is well recognized that the Medical Information (MI) department is a key externally facing function that needs to maintain a consistent focus on optimizing its capabilities of addressing product medical inquiries worldwide. Methods: In the United States, a consortium namedPha rmaC ollaboration forT ransparentM edicalI nformation, phactMI, a collaboration of pharmaceutical company MI departments dedicated to supporting health care professionals in their commitment to provide quality patient care, has provided a forum to benchmark and share best practices across the companies. In May 2017, phactMI conducted a survey inclusive of 25 biopharmaceutical companies to gain insight into the globalization of respective MI departments and relevant trends. Results: We found increased trends in various aspects of globalization across large, mid, and small size companies, and identified key drivers for success. Overall, 16 of the 25 companies had globalized their MI department, 5 had only partially globalized, and the remaining 4 had not globalized. Conclusion: The findings of this survey will further help inform the MI community as to globalization approaches for a successful outcome.